2015
DOI: 10.5152/tud.2015.22120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between ciprofloxacin and trimethoprim-sulfamethoxazole in antibiotic prophylaxis for transrectal prostate biopsy

Abstract: Objective: The aim of this study was to compare the efficacies of oral ciprofloxacin administration and oral trimethoprim-sulfamethoxazole (TMP-SMX) regimens in preventing infectious complications following transrectal ultrasound guided biopsy of the prostate. Material and methods:Between 2011-2013, the medical records of 391 (mean age 64.62±7.64 years; range 40 to 87 years) patients who underwent transrectal prostate biopsies, due to suspicion of prostate cancer were retrospectively reviewed. While 500 mg cip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…In another study, a positive urine culture was observed in 4% of the patients in the ciprofloxacin group and in 2.8% of the patients in the TMP-SMX group. There was no significant difference in comparison of the two antibiotics (16) . Although antibiotic treatment was given before and after transrectal prostate biopsy, E. coli meningitis has been reported in the literature, so it is necessary to perform the TRUS-PB procedure within a certain discipline (17) .…”
Section: Discussionmentioning
confidence: 72%
“…In another study, a positive urine culture was observed in 4% of the patients in the ciprofloxacin group and in 2.8% of the patients in the TMP-SMX group. There was no significant difference in comparison of the two antibiotics (16) . Although antibiotic treatment was given before and after transrectal prostate biopsy, E. coli meningitis has been reported in the literature, so it is necessary to perform the TRUS-PB procedure within a certain discipline (17) .…”
Section: Discussionmentioning
confidence: 72%
“…[6,15] In multi-center studies where patients with urinary infection have been evaluated in many geographic regions of Turkey, rates of quinolone-resistance of E. coli strains isolated from urine cultures have been reported to range between 8.3, and 38 percent. [16,17] In a study by Atılgan et al [18] urine culture positivity was detected in 13 (3.3%) patients, and growth of E. coli was detected in all of these cultures. [18] Feliciano et al [6] reported infectious complication rate of 2.4% (1% in febrile cases) in patients in whom fluoroquinolone was used for prophylaxis.…”
Section: Discussionmentioning
confidence: 94%
“…[16,17] In a study by Atılgan et al [18] urine culture positivity was detected in 13 (3.3%) patients, and growth of E. coli was detected in all of these cultures. [18] Feliciano et al [6] reported infectious complication rate of 2.4% (1% in febrile cases) in patients in whom fluoroquinolone was used for prophylaxis. In the same study, in 17 of 19 patients with positive urine cultures, growth of E.coli was observed.…”
Section: Discussionmentioning
confidence: 94%
“…The use of fluoroquinolones as standard is supported by two meta-analyses showing that fluoroquinolones have significantly better effects compared with placebo in all included trials 3,7 . Other antibiotic agents that have been investigated alone or in addition to fluoroquinolones include trimethoprim-sulfamethoxazole, gentamicin, fosfomycin, piperacillin-tazobactam, amikacin, ceftriaxone, amoxicillin-clavulanate and meropenem 3,6,7,[21][22][23][24] . Most regiments appear to reduce the risk of infection but there is a lack of sufficiently powered randomized trials comparing fluoroquinolones to other antibiotic classes 7 .…”
Section: Discussionmentioning
confidence: 99%